2009
DOI: 10.4088/jcp.08m04638blu
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Brain Stimulation With High-Frequency and Low-Intensity Repetitive Transcranial Magnetic Stimulation Treatment for Posttraumatic Stress Disorder

Abstract: Objective-We aimed to investigate the efficacy of 20 Hz repetitive transcranial magnetic stimulation (rTMS) of either right or left dorsolateral prefrontal cortex (DLPFC) as compared to sham rTMS for the relief of posttraumatic stress disorder (PTSD)-associated symptoms.Method-In this double-blind, placebo-controlled phase II trial conducted between October 2005 and July 2008, 30 patients with DSM-IV-diagnosed PTSD were randomly assigned to receive 1 of the following treatments: active 20 Hz rTMS of the right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
191
1
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(206 citation statements)
references
References 44 publications
(37 reference statements)
8
191
1
6
Order By: Relevance
“…Accordingly, we determined whether rTMS, a well-established therapeutic method PTSD treatment, offered benefits as early intervention after stress. Prior studies have indicated that administration of high-frequency rTMS to the right dorsolateral prefrontal cortex is beneficial for ameliorating PTSD symptoms [26,27]. Our data presented herein demonstrated for the first time that chronic administration of rTMS has anxiolytic effect on stressrelated anxiety-like behaviors without affecting control rats.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Accordingly, we determined whether rTMS, a well-established therapeutic method PTSD treatment, offered benefits as early intervention after stress. Prior studies have indicated that administration of high-frequency rTMS to the right dorsolateral prefrontal cortex is beneficial for ameliorating PTSD symptoms [26,27]. Our data presented herein demonstrated for the first time that chronic administration of rTMS has anxiolytic effect on stressrelated anxiety-like behaviors without affecting control rats.…”
Section: Discussionsupporting
confidence: 51%
“…In the first, action precedes the stress with the intention of enhancing resistance to stress while in the second rTMS on Model Rat of PTSD approach, treatment is introduced after in order to prevent establishment of a stress related syndrome [27]. Since many traumatic incidents are unpredictable, the latter approach is likely the one that is feasible.…”
Section: Discussionmentioning
confidence: 99%
“…18 Modulation of prefrontal cortex can alleviate the core symptoms of Post Traumatic Stress Disorder and suggest that high-frequency rTMS of right prefrontal cortex might be the optimal treatment strategy. 19 Another study confirms that five daily sessions of high frequency rTMS over the left and then the right prefrontal cortex improves cognitive function in patients with mild to moderate degree of Alzheimer's Disease. 20 Adverse effects: Although TMS is generally regarded as safe, …”
Section: Tms Can Suppress Cortical Excitation Possibly Throughmentioning
confidence: 49%
“…Показана эффективность низкочастотной стимуля-ции правой DLPFC при генерализованном тревожном расстройстве [159]; высокочастотной -как левой, так и правой DLPFC при посттравматическом тревожном рас-стройстве [160]; высокочастотной -левой DLPFC и низ-кочастотной -зоны SMA при обсессивно-компульсив-ном расстройстве [161,162]. При паническом расстрой-стве достоверных различий по сравнению с группой ими-тации стимуляции получено не было [163].…”
Section: тревожное расстройствоunclassified